2009
DOI: 10.1002/ajmg.a.32831
|View full text |Cite
|
Sign up to set email alerts
|

The ring 14 syndrome: Clinical and molecular definition

Abstract: The ring 14 (r14) syndrome is a rare condition, whose precise clinical and genetic characterization is still lacking. We analyzed a total of 20 patients with r14 and another 9 patients with a linear 14q deletion. The ring was complete, with no apparent loss of chromosome material, in 6 cases; a terminal 14q deletion, varying in size from 0.65 to 5 Mb, was detected in the remaining 14 cases. Deleted ring chromosomes were 70% paternal and 30% maternal. UPD (14) was never detected. With respect to the linear 14q … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 9 publications
6
70
1
2
Order By: Relevance
“…However, our patient is now seizure free following treatment. The relatively constant clinical feature of seizures may manifest in various forms [Schlade-Bartusiak et al, 2005;Ville et al, 2009;Zollino et al, 2009], and usually appears between 1 month and 4 years of age [Zelante et al, 1991;Shirasaka et al, 1992;Ono et al, 1999;Morimoto et al, 2003]. Also, both patients reported by Morimoto et al [2003] and Ono et al [1999] showed generalized tonic-clonic convulsions that are similar to our patient and others reported in the literature as drug resistant.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, our patient is now seizure free following treatment. The relatively constant clinical feature of seizures may manifest in various forms [Schlade-Bartusiak et al, 2005;Ville et al, 2009;Zollino et al, 2009], and usually appears between 1 month and 4 years of age [Zelante et al, 1991;Shirasaka et al, 1992;Ono et al, 1999;Morimoto et al, 2003]. Also, both patients reported by Morimoto et al [2003] and Ono et al [1999] showed generalized tonic-clonic convulsions that are similar to our patient and others reported in the literature as drug resistant.…”
Section: Discussionsupporting
confidence: 84%
“…His head circumference is currently within the normal range, although at the lower limit (0.4th-2nd centiles). Among the anomalies found in our patient, there are two features which were present in almost all cases of ring 14 syndrome: seizures and abnormal retinal pigmentation [Zollino et al, 2009]. Interestingly, these characteristics usually present in ring 14 patients regardless of the ring chromosome size and composition.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…However, some rarer defects were also detected, as seen in patient G10.1 who showed a rare de novo deletion at 14q32.33. Only 25 cases of distal 14q23.3 deletion are reported in the literature to date [Miller et al, 1992;van Karnebeek et al, 2002;Maurin et al, 2006;Zollino et al, 2009;Wu et al, 2010;Engels et al, 2012;Holder et al, 2012]. Individuals bearing this deletion show common clinical characteristics including cardiac defects, developmental delay, microcephaly, high forehead with lateral hypertrichosis, hypotonia, high palate, broad nasal bridge, thin upper lip, single palmar crease, micrognathia, and ophthalmological problems [Maurin et al, 2006;Zollino et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Usually the phenotype of ring chromosome patients overlaps that of the deletion of both ends of the respective chromosome syndromes (Schinzel, 2001). Nevertheless, the phenotypes associated with ring chromosomes are highly variable, since -in addition to the primary deletions associated with ring formation -secondary loss or gain of material may have occurred, due to the instability of ring chromosomes in general (Tümer et al, 2004;Purandare et al, 2005;Glass et al, 2006;Höckner et al, 2008;Zollino et al, 2009). Thus, the phenotype will actually depend on the size of the ring chromosome, the amount of euchromatin lost during ring formation, the ring stability, the presence of secondary aneuploid cells, and the rate of mosaicism (Kosztolányi, 1987a;Le Caigne et al, 2004).…”
Section: Introductionmentioning
confidence: 99%